International law and commercial surrogacy: forbid or allow - Seidinova, M.A. (Bulletin of the Karaganda University “Law Series”, 2023)
The intensive development of international commercial surrogacy agreements has created serious ethical and legal dilemmas regarding the citizenship of children born by surrogate mothers and the paternity of children conceived under the terms of commercial surrogacy, as well as the potential exploitation of surrogate mothers. This article examines these dilemmas through the lens of international human rights law to determine whether a state should adopt a prohibitive or permissive approach to this practice. In the article, the author defines commercial surrogacy as the practice or arrangement whereby the intended parent(s) pay the surrogate mother, directly or through an intermediary, a financial reward in addition to the actual out-of-pocket expenses incurred by the surrogate mother. It is argued that the right to privacy is broad enough to cover the right to enter into a surrogacy agreement. However, states may restrict this right if necessary to protect the rights of others and/or protect public morals. In this context, commercial surrogacy is problematic for several reasons. First, there are good reasons to believe that this amounts to the sale of a child. Second, there are arguments that commercial surrogacy is morally unacceptable because it reinforces gender inequality. It is difficult to provide sufficient protection against the potential exploitation of surrogate mothers (especially in developing countries, where women often accept commercial surrogacy due to poverty). If either of these arguments is accepted, then under international law states can be required to ban commercial surrogacy. Moreover, even if these arguments remain controversial, provided to states in fulfilling their human rights obligations are such that they can still rely on these arguments to justify a ban on commercial surrogacy. This finding has serious implications for any potential multilateral treaty governing international commercial surrogacy, unless it prohibits the practice, in which case its usefulness would be limited given the little or no demand for international altruistic surrogacy.